Pengaruh Informasi Akuntansi terhadap Harga Saham Serta Dampaknya terhadap PBV pada Sub Sektor Farmasi yang Terdaftar di BEI - Khairul Azwar; Elly Susanti; Widia Astuty (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
This research was conducted to determine the effect of accounting information on stock prices and their impact on PBV. Data analysis techniques with path analysis. This research is in the pharmaceutical sub-sector. The results of the F test study, obtained independent variables affect the dependent variable. In t-test accounting information does not have a significant effect on stock prices, while the ROE variable has an effect on stock prices. Furthermore, for stock prices, there is no impact between the influence of accounting information on PBV